Introduction to business (McGraw-Hill Higher Education, 2009)
Constellations have helped break up space into manageable pieces to aid navigation. By connecting the stars we can relate to the unknown providing a guide to reach our destination. This title guides students through topics by dividing each into smaller sections encouraging student understanding and building confidence.